Cell wall perturbation sensitizes fungi to the antimalarial drug chloroquine - Islahudin, Farida; Khozoie, Combiz; Bates, Steven; Ting, Kang-Nee; Pleass, Richard J.; Avery, Simon V. (American Society for Microbiology, 2013)
Chloroquine (CQ) has been a mainstay of antimalarial drug treatment for several decades. Additional therapeutic actions of CQ have been described, including some reports of fungal inhibition. Here we investigated the action of CQ in fungi, including the yeast model Saccharomyces cerevisiae. A genomewide yeast deletion strain collection was screened against CQ, revealing that bck1Δ and slt2Δ mutants of the cell wall integrity pathway are CQ hypersensitive. This phenotype was rescued with sorbitol, consistent with cell wall involvement. The cell wall-targeting agent caffeine caused hypersensitivity to CQ, as did cell wall perturbation by sonication. The phenotypes were not caused by CQ-induced changes to cell wall components. Instead, CQ accumulated to higher levels in cells with perturbed cell walls: CQ uptake was 2- to 3-fold greater in bck1Δ and slt2Δ mutants than in wild-type yeast. CQ toxicity was synergistic with that of the major cell wall-targeting antifungal drug, caspofungin. The MIC of caspofungin against the yeast pathogen Candida albicans was decreased 2-fold by 250 μM CQ and up to 8-fold at higher CQ concentrations. Similar effects were seen in Candida glabrata and Aspergillus fumigatus. The results show that the cell wall is critical for CQ resistance in fungi and suggest that combination treatments with cell wall-targeting drugs could have potential for antifungal treatment.